Unity of the Universe: New and Global Theory Correlating the Ratio of Hydrogen - Helium to Dark Energy – Matter: Sayed`s Golden Formula (SGF) - El-Mongy, Sayed (JOURNAL OF ADVANCES IN PHYSICS, 2022)
Singularity and unity is the glorified Creator of the universe. This article went deeply through hydrogen and helium percentages in the universe to explain and correlate their existence with dark energy and matter. Our finding indicates that the hydrogen to helium (H/He) ratio in the universe should be and equal to π. Our previous work predicted that the dark energy to dark matter (DE/DM) ratio is also equal π. It was deduced that the ratio of hydrogen and helium to dark energy and matter (H/He)/(DE/DM) is correlated. This ratio, which is called S-ratio, was simply estimated and found to be unity. It was also observed that the iron of mass number 56 is also in correlation with hydrogen and helium content; the ratio is specifically equal √π. This work is uniquely correlated the estimated (H/He)/(DE/DM) ratio with the Golden ratio to produce a new global formula to be defined as Sayed Golden formula (SGF). The value of SGF is 1.71347. The results of H/He were compared with many of the other published works.